Editorial - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2010)
Sorry, no abstract available. Please click on the PDF button below to get to the editorial.